6.28 THE TECHNICAL CONDITION OF THE ELEMENTS OF THE UPPER STRUCTURE OF THE HIGH-SPEED HIGHWAY PATH - Makhamajanov Shukhratjon Shavkat ugli, Umaraliev Shahjahan Mukhammadrozi ugli, Tadjibaev Sherzod Amirkulovich, Abdualiev Elyorbek Begali ugli. (Innovative technologies in construction Scientific Journal, 2024)
The article presents the technical parameters of high-speed highways under several conditions, their use and requirements for the path. The elements of the upper structure of the track used on the HSR and data on train safety are described. Keywords: HSR, rail, whip, fastening, ballast layer. Rails with a running weight of at least 60 kg are used on the HSR, welded together (joint-less track) in long and extra-long lashes. Rails are subject to increased requirements in terms of their strength characteristics and straightness. The curvature of the rails in the vertical and horizontal planes should not exceed 0.3 mm based on a measurement of 1.5 m [1.2.3.4.5.6]. The rail lashes of the jointless track must be welded from new short rail lashes or P65 rails with a length of at least 23.5 m of category B, T1, meeting the requirements [2]. Long-length lashes are delivered to the place of laying on the way by trains from special platforms (Fig. 1). Fig. 1. Transportation of rail lashes to the installation site As on conventional railways, on the HSR, the connection of rails with a sub–rail base - sleepers or reinforced concrete slabs, is carried out by rail fasteners. On high-speed highways, they must meet the requirements of ensuring a normalized elastic connection (degree of compression) of rails with a sub-rail base and damping of force influences in the wheel-rail system, be reliable, durable, suitable for mechanized installation, convenient for maintenance and repair of the track. To date, various types of elastic fasteners are used on railways in the world (Fig. 2), fasteners with bar terminals have become widespread: bolt-free anchor of the Pandrol company and screw-dowel companies of the Vossloh company. Bar terminals have high strength and rigidity, are reliable, maintain track stability, and are relatively protected from vandalism. The intermediate fastening should ensure stable vertical pressing of the rail to the base with a force of at least 20 kN, the resistance to longitudinal shear of the rail in the fastening node should be at least 12.5 kN [7.8.9.10.11.12.13]. The recorded speed record for electric trains – 574.8 km/h (2007 France) was set on a railway track with “Pandrol-Fastklip” type fasteners. Fig. 2. Elastic rail fasteners for reinforced concrete sleepers: the anchor bond “Pandrol" and the bond “Vossloh".Currently, two structures of the upper structure of the track have been used on high-speed railways: a rail sleeper with reinforced concrete sleepers laid on ballast and a reinforced concrete sub-rail base.With the traditional type of under-rail base using ballast, the rails are laid on reinforced concrete sleepers. Reinforced concrete sleepers with a plot of 1,840 pieces per 1 km should be laid on the way. The rail grating is laid on a 35-40 cm thick ballast layer of crushed stone (granite, basalt, diabase) with a fraction size of 25-60 mm.Sleepers are laid on a layer of crushed stone with a thickness of 35-40 cm, usually consisting of fractions of 25-60 mm. A pillow with a thickness of at least 15 cm is arranged under the rubble from a sand-gravel mixture or crushed stone of a fraction of 5-25 mm. Instead of a pillow, a protective layer of polymer materials can be laid. The shoulder of the ballast prism is at least 45 cm, the slope is 1:1.5.